Energy and speleogenesis: Key determinants of terrestrial species richness in caves. Issue 23 (24th October 2017) - Jiménez‐Valverde, Alberto; Sendra, Alberto; Garay, Policarp; Reboleira, Ana Sofia P. S.
Abstract: The aim of this study was to unravel the relative role played by speleogenesis (i.e., the process in which a cave is formed), landscape‐scale variables, and geophysical factors in the determination of species richness in caves. Biological inventories from 21 caves located in the southeastern Iberian Peninsula along with partial least square (PLS) regression analysis were used to assess the relative importance of the different explanatory variables. The caves were grouped according to the similarity in their species composition; the effect that spatial distance could have on similarity was also studied using correlation between matrices. The energy and speleogenesis of caves accounted for 44.3% of the variation in species richness. The trophic level of each cave was the most significant factor in PLS regression analysis, and epigenic caves (i.e., those formed by the action of percolating water) had significantly more species than hypogenic ones (i.e., those formed by the action of upward flows in confined aquifers). Dissimilarity among the caves was very high (multiple‐site βsim  = 0.92). Two main groups of caves were revealed through the cluster analysis, one formed by the western caves and the other by the eastern ones. The significant—but low—correlation found between faunistic dissimilarity and geographical distance ( r  =   .16) disappeared once the caves were split into the two groups. The extreme beta‐diversity suggests a very low connection among the caves and/or a very low dispersal capacity of the species. In the region under study, two main factors are intimately related to the richness of terrestrial subterranean species in caves: the amount of organic material (trophic level) and the formation process (genesis). This is the first time that the history of a cave genesis has been quantitatively considered to assess its importance in explaining richness patterns in comparison with other factors more widely recognized. Abstract : In the Prebaetic system, two main factors are intimately related to the richness of terrestrial subterranean species in caves: the amount of organic material and the formation process. This is the first time that the history of caves genesis is explicitly and quantitatively considered to assess its relative importance in comparison with other factors more widely recognized.